Study of Information Behavior of Reference Librarians at The Diponegoro University Library - Aeni, Siti Nur; Prasetyawan, Yanuar Yoga (Edulib, 2021)
This study aims to determine the information behavior of reference librarians in meeting users' information needs at the Diponegoro University Library. The research method used in this study is a qualitative research method with a case study approach. Data collection techniques used in this study are observation, interviews, and documentation. Researchers have interviewed six informants. The data analysis method used is by using thematic analysis method. The results showed that the information behavior carried out by reference librarians in meeting users' information needs at the Diponegoro University Library can be seen when reference librarians can help users meet their information needs. Information behavior carried out by reference librarians in helping users meet their information needs can be done by providing reference services at the Diponegoro University Library, knowing and meeting users' information needs. Reference librarians can also assist users in meeting their information needs by guiding users on how to search for information by the information needs of users quickly and precisely.